Liquid-Based Cytopathology Test: A Novel Method for Diagnosing Pulmonary Mucormycosis in Bronchial Brushing Samples - Jiang, Xiaolin; Yang, Tian; Li, Qiyuan; Zhu, Xianglan; Su, Xueying; Li, Jinnan; Jiang, Yong (Frontiers in Microbiology, 2018)
Background: Pulmonary mucormycosis, a relatively rare but severe pulmonary fungal disease with a high mortality rate, is difficult to diagnose in immunocompromised patients. Conventional cytopathology (CCP) examination of respiratory samples can help detect Mucorales, but its diagnostic sensitivity is poor. The aim of this study was to assess the first application of liquid-based cytopathology test (LCT) to detect Mucorales. Methods: A total of 33 pairs of bronchial brushing samples from 27 patients diagnosed as pulmonary mucormycosis by fiberoptic bronchoscopy biopsy were prepared as slides using both CCP and LCT. LCT and CCP used the same cytology brush to obtain samples at the same site during the same time as the fiberoptic bronchoscopy biopsy. All samples were stained with Papanicolaou, GMS and PAS. CCP and LCT slides were evaluated from the rate of positive detection, 8 cytomorphological features and 7 background features. Results: LCT-prepared slides showed a higher positive rate of Mucorales detection than CCP-prepared slides for Papanicolaou’s staining [28/33 (84.85%) vs. 15/33 (45.45%), p = 0.001] and for “special staining” with GMS and PAS [29/33 (87.88%) vs. 18/33 (54.55%), p = 0.003]. Clearer smear background and more distinct stereoscopic cytopathological features were observed in LCT. Messy yarn-like necrosis observed in conventionally prepared 75.76% (25/33) samples was cytomorphological suggestive for the diagnosis of mucormycosis. Conclusion: This retrospective study suggests that LCT may be better than CCP to detect Mucorales in bronchial brushing samples from patients with pulmonary mucormycosis.